Types of emotional self-regulation of women who have suffered from psychological abuse in the family - Kocherhina, Iryna (Journal of Education Culture and Society, 2018)
Aim. The aim of the paper is to present the results of research on the types of emotional self-regulation of women who have suffered from psychological abuse in family relations.Methods. 140 Ukrainian women who suffered from psychological abuse in the family were interviewed. For the analysis of the obtained results, methods of statistical processing of data were used.Results. It has been established that women who were victims of psychological abuse from members of their family may have different types of emotional self-regulation: "Emotionally unstable," "Adaptive," "Spontaneous." It is shown that women with emotionally unstable types of emotional self-regulation are emotionally unstable during psychological abuse in the family, which is manifested in their anxiety, tension, depression, self-criticism. It is said that women who are referred to as having the adaptive type of emotional self-regulation possess a sufficient level of neuropsychic stability and self-control and it has been established that women who are characterized by a spontaneous type of emotional self-regulation, when exposed to psychological abuse, have a low level of self-control, which indicates spontaneity and impulsivity in relationships with others.Conclusions. Еmotional self-regulation does not act as a tool to cancel negative experiences, but it is a change in these experiences for other that helps to optimize their condition. Еmotional self-regulation and the ability to manage one's own psychical state for the preservation of mental health are important in the context of psychological abuse in the family. Furthermore, it is emphasised on different types of emotional self-regulation of women in situations of psychological abuse in the family.